Kelayakan E-Modul Submateri Pemanfaatan Keanekaragaman Hayati - Aisyah; Dra. Syamswisna, M. Si; Titin, S. Pd. Si., M. Pd (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
The purpose of this study was to test the feasibility or not of e-module teaching materials for the use of biodiversity in class X high school. E-modules are created sourced from the results of an inventory of plants that are useful as natural cosmetics in Mega Blora Hamlet, Kubu Raya Regency. The research method applied is descriptive quantitative which is carried out with the steps of plant inventory, making e-module teaching materials, validation of teaching materials and data analysis. The validity test of the e-module of cosmetic plants is measured through four aspects, namely proportionality, grinding, content validity and fertility, which contains 16 criteria. The e-module validators were 2 biology education lecturers and 3 high school class X biology teachers selected through purposive sampling method, namely SMAN 1 Sungai Ambawang, SMAN 12 Pontianak and SMAN 1 Siantan. In the analysis, the data were examined based on the formula CVR and CVI according to Lawshe (1975) so obtained the result CVR 0.99 and the result CVI 0.99, which means that the teaching material of the electronic module is declared valid or worthy to be applied as a learning resource to the sub-material of biodiversity utilization of class X high school.